PUBLIC POLITICS REGARDING THE PENSION SYSTEM - Liviu RADU; Carmen RADU (Challenges of the Knowledge Society)
The said paper proposes to seak some answers regarding the long term sustainability of the pension system. Romania’s pension system originates from the invalidity insurances and pension system designed by the German cancellor Otto Eduard Leopold von Bismark in 1889. From a European perspective, Romania has to fill an obvious gap regarding the reformation of the national public pension system. International experience, particularly of the last 130 years, indicates that, in actuality, multiple pension systems have been put into function in most of the world’s countries and which are diferenciated by some elements (organizing and managing the system, defyning pension rights, method of forming the resources, the pension’s level rapported to the average income etc.) and after the eficacity degree dependent on internal influences, social, economic and demographic environment, and last but not least by the political factor.